Assessment of Terrestrial Small Mammals in an Agro-industrial Company Concession, Western Liberia - Akpatou, Kouame Bertin; Bohoussou, Kouakou Hilaire; Bene, Koffi Jean-Claude (International Journal of Applied Sciences and Biotechnology, 2019)
This study was conducted in a global context of biological assessment of potential oil palm plantation development in western Liberia. It has been recommended as a complementary study to design a biological baseline prior to the development of oil palm plantations. It is based on "Terrestrial small mammals” biological model. Thus, terrestrial small mammal richness and abundance were assessed in Sime Darby palm oil company Concession at Bong and Gbarpolu counties in western Liberia. Conventional live-trapped methods using mainly pitfalls and Sherman trapswere used to investigate terrestrial small mammals. The combination of these two methods allowed the capture of 76 specimens belonging to 11 species.The most frequent species was Crocidura jouvenetae(39.47 %) followed by Hylomyscus simus(14.47 %) and Hybomys planifrons(10.53 %). Small mammal communities wereglobally dominated by forest species (Crocidura eburnea, Crocidura jouvenetae, Crocidura muricauda, Crocidura obscurior, Dephomys defua, Hybomys planifrons, Hylomyscus simusand Mus setulosus), which indicates the lower level of forest degradation at this area. These species of rodent and shrew are threatened to disappear due to the conversion of their habitats to palm oil plantations. It is highly recommended that the company preserve intact primary forest relics within oil palm plantations in order to conserve representative sample local biodiversity. Int. J. Appl. Sci. Biotechnol. Vol 7(4): 434-439